History and Jurisprudence of the Maqāṣid: A Critical Appraisal (American Journal of Islam and Society, 2022)
This article, which was originally delivered as a keynote address at the AJIS symposium on “Theory and Uses of Maqāṣid al-Sharī‘a” in May 2021, begins with a review of the Qur’an and Sunna on the maqāṣid, followed by a similar review of the history of maqāṣid and salient contributors to its jurisprudence, while drawing attention to its prolonged marginalization in legal theory. The recent revival of maqāṣid in the latter part of the twentieth century is reviewed next, followed by a note on the special appeal of the maqāṣid, the end of their historical neglect, and a great deal of renewed interest by contemporary Muslim scholars. The relationship of uṣūl al-fiqh to maqāṣid has also been the subject of renewed interest, as to whether it is one of continued domination or one of complementarity between them. Then follows a section on the classification of maqāṣid, how they are appraised and prioritized in relationship to one another; and a review of methodological indicators that can help withthe appraisal and ranking of the maqāṣid and their application to new issues. The article concludes with an account of ijtihād maqāṣidi and its application to contemporary issues.